Politik Hukum Putusan Mahkamah Konstitusi Nomor : 46/PUU-VIII/2010 Tentang Status Anak di Luar Perkawinan Perspektif Siyasah Syar’iyyah - Jauhari Jauhari; Muhammad Burhan; Ulya Kencana (Universitas Sriwijaya, 2019)
Legal politics of the Constitutional Court Decision Number 46 / PUU-VIII / 2010 concerning the status of children outside of marriage is that Article 43 of Law Number 1 of 1974 which reads